Surabaya land cover prediction based on Landsat Satellite using the Multi-layer Perceptron Method - Prayuda, Shanas Septy; Kusuma, Maritha Nilam (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
Infrastructure development has occurred very rapidly in Surabaya in the last few decades. There is pressure on the need for land use in line with the increase in population. This study aims to analyze changes in land cover with inter-decade analysis and predict land cover in 2021-2030 in Surabaya using the Multi-Layer Perceptron method. The data used in this research is Landsat satellite which is considered good in representing the actual land cover. A decrease in the amount of vegetation occurs every decade in Surabaya, while the number of buildings is increasing and the bodies of water are relatively the same. The Multi-Layer Perceptron method has a good level of accuracy in predicting land cover in the city of Surabaya. In 2021-2030 it is predicted that Surabaya will still experience an increase in the number of buildings and a decrease in the amount of vegetation.